Remarks on the euro crisis - Hans-Eggert Reimers (Hochschule Wismar, Fakultät für Wirtschaftswissenschaften, 2013)
[Introduction] The euro crisis evolves out of the global financial crisis, which erupted with the collapse of Lehman Brothers in September 2008. Starting point of the euro crisis was the statement of the Greek government in autumn 2009 that budget deficit may be much higher than announce in the beginning of 2009. In early 2010 financial market expectations pointed in direction of possible Greek sovereign default. In May 2010 some secondary markets for government bonds began to dry up completely and the EU council agreed to a rescue plan for Greece. This plan could not dam up the concerns regarding the debt situation in Portugal and Ireland. During the ongoing crisis process these countries are supported by rescue plans (see Todev, Brazda, Laurinkari 2013). Rescue plans are not an instrument of the legal arrangement of the European Union or of the Eurozone. Therefore, new arrangement has had to be established since then. Moreover, the euro crisis is not only a sovereign debt crisis. It contains at least a banking crisis and macroeconomic crisis. All these parts are strongly connected. In the paper the main links are described. Furthermore, new legal arrangements and developments are presented to handle the sovereign debt, banking and macroeconomic crisis. In the beginning the changes deals with the sovereign debt crisis. Countries, which got support of other countries, had to accept changes in their public budget structure. To some extend the policy changes should help to solve reasons of the debt situation and of the macroeconomic crisis. In 2012 the EU council focused on the banking crisis, where the EU agreed to establish a banking union. The macroeconomic crisis is apparent by high unemployment rates and real GDP decreases. One main reason behind these characteristics is the lack of competitiveness of some economies. This point is addressed in the paper. At the end of the paper political aspects of the crisis politics should be mentioned. It is dealing with the income and wealth situation of some EU countries.
Keywords: K32; L92; Q51; 330